Perubahan kadar LDL dan HDL pada kelinci New Zealand White yang diberi ekstrak beras hitam (Oryza sativa L.) - Runtu, Jessica G.; Kawengian, Shirley E.S.; Mayulu, Nelly; Bolang, Alexander S.L. (Universitas Sam Ratulangi, 2016)
Abstract: Cardiovascular disease, especially coronary heart disease (CHD), is the leading cause of death annually. Low HDL and high LDL levels are related to the increased risk of CHD. Polyphenol such as anthocyanin in black rice could reduce the cardiovascular risks due to its antioxidant that has anti-platelet and anti-inflammatory activities. This study was aimed to determine the changes in LDL and HDL levels in rabbits fed with black rice extract (Oryza sativa L.). This was a true experimental study with a pretest posttest control group design. Samples were male New Zealand White rabbits, weighing 0.8-2.5 kg divided into four groups. Group A was fed with standard diet; group B was fed with high-fat diet; group C was fed with high-fat diet and black rice extract; and group D was fed with high-fat diet and atorvastatin. Data were presented descriptively. The results showed that the mean LDL level of group C increased by 6.5 mg/dl but one sample showed a decrease of 2 mg/dl. The mean level of HDL of group C decreased 0.50 mg/dl. This reduction was not as many as the other groups but one sample showed an increase of 5 mg/dl. Conclusion: Not all rabbits fed with black rice extract showed decreased LDL level and increased HDL level.Keywords: LDL, HDL, black rice extractÂ Abstrak: Penyakit kardiovaskuler terutama penyakit jantung koroner (PJK) merupakan penyebab kematian tertinggi pertahunnya. Kadar HDL rendah serta kadar LDL tinggi berkaitan dengan meningkatnya risiko PJK. Polifenol seperti antosianin yang terdapat dalam beras hitam dapat menurunkan risiko penyakit kardiovaskular karena antioksidannya dengan aktivitas anti-platelet dan anti-inflamasi. Penelitian ini bertujuan untuk mengetahui perubahan kadar LDL dan HDL pada kelinci yang diberi ekstrak beras hitam (Oryza sativa L.). Jenis penelitian ialah true experimental dengan desain pre test post test control grup. Sampel ialah kelinci New Zealand White jantan, berat badan 0,8- 2,5 kg. Kelompok A diberi pakan standar; kelompok B diberi diet tinggi lemak; kelompok C diberi diet tinggi lemak dan ekstrak beras hitam; dan kelompok D diberi diet tinggi lemak dan atorvastatin. Data disajikan secara deskriptif. Hasil penelitian mendapatkan pada kelompok C, rerata kadar LDL meningkat 6,5 mg/dl tetapi satu sampel mengalami penurunan sebesar 2 mg/dl. Rerata kadar HDL pada kelompok C menurun 0,50 mg/dl; penurunan ini tidak sebesar pada kelompok lainnya tetapi satu sampel mengalami peningkatan sebesar 5 mg/dl. Simpulan: Kelinci yang diberi ekstrak beras hitam tidak semua mengalami penurunan kadar LDL dan peningkatan kadar HDL. Kata kunci: LDL, HDL, Ekstrak beras hitam